Evidence for a Diagenetic Origin of Vera Rubin Ridge, Gale Crater, Mars: Summary and Synthesis of Curiosity's Exploration Campaign - Fraeman, A. A.; Edgar, L. A.; Rampe, E. B.; Thompson, L. M.; Frydenvang, J.; Fedo, C. M.; Catalano, J. G.; Dietrich, W. E.; Gabriel, T. S. J.; Vasavada, A. R.; Grotzinger, J. P.; L'Haridon, J.; et al. (Journal of geophysical research. Planets, 2020)
This paper provides an overview of the Curiosity rover's exploration at Vera Rubin ridge (VRR) and summarizes the science results. VRR is a distinct geomorphic feature on lower Aeolis Mons (informally known as Mount Sharp) that was identified in orbital data based on its distinct texture, topographic expression, and association with a hematite spectral signature. Curiosity conducted extensive remote sensing observations, acquired data on dozens of contact science targets, and drilled three outcrop samples from the ridge, as well as one outcrop sample immediately below the ridge. Our observations indicate that strata composing VRR were deposited in a predominantly lacustrine setting and are part of the Murray formation. The rocks within the ridge are chemically in family with underlying Murray formation strata. Red hematite is dispersed throughout much of the VRR bedrock, and this is the source of the orbital spectral detection. Gray hematite is also present in isolated, gray‐colored patches concentrated toward the upper elevations of VRR, and these gray patches also contain small, dark Fe‐rich nodules. We propose that VRR formed when diagenetic event(s) preferentially hardened rocks, which were subsequently eroded into a ridge by wind. Diagenesis also led to enhanced crystallization and/or cementation that deepened the ferric‐related spectral absorptions on the ridge, which helped make them readily distinguishable from orbit. Results add to existing evidence of protracted aqueous environments at Gale crater and give new insight into how diagenesis shaped Mars' rock record. Plain Language Summary Vera Rubin ridge is a feature at the base of Mount Sharp with a distinct texture and topography. Orbiter observations showed hematite, a mineral that sometimes forms by chemical reactions in water environments, was present atop the ridge. The presence of both water and chemical activity suggested the area preserved a past habitable environment. In this paper, we detail how the Curiosity science team tested this and other orbital‐based hypotheses. Curiosity data suggested that most ridge rocks were lain down in an ancient lake and had similar compositions to other Mount Sharp rocks. Curiosity confirmed that hematite was present in the ridge but no more abundantly than elsewhere. Larger grain size or higher crystallinity probably account for the ridge's hematite being more visible from orbit. We conclude Vera Rubin ridge formed because groundwater recrystallized and hardened the rocks that now make up the ridge. Wind subsequently sculpted and eroded Mount Sharp, leaving the harder ridge rocks standing because they resisted erosion compared with surrounding rocks. The implication of these results is that liquid water was present at Mount Sharp for a very long time, not only when the crater held a lake but also much later, likely as groundwater. Key Points We summarize Curiosity's campaign at Vera Rubin ridge (Sols 1726–2302) and the high‐level results from articles in this special issue Vera Rubin ridge formed when diagenesis hardened rocks along the base of Aeolis Mons; wind subsequently etched the feature into a ridge Results add evidence for protracted aqueous environments at Gale crater and give new insight into how diagenesis shaped Mars' rock record